Efektivitas Sabun Transparan Antibakteri Ekstrak Etanol Sawi Putih (Brassica Rapa Subspesies. Pekinensis) Dengan Kombinasi Coconut Oil dan Castor Oil: The Effectiveness of Antibacterial Transparent Soap Ethanol Extract of Chilli (Brassica Rapa Subspecies. Pekinensis) With a Combination of Coconut Oil and Castor Oil - Khusniyah, Nurul; Rohmah, Jamilatur (Medicra (Journal of Medical Laboratory Science/Technology), 2019)
This study aims to determine the best soap formula and to know the effect of addition of chicory extract (Brassica rapa subspecies, pekinensis) in transparent solid soap supply of antibacterial extract of chicory extract (Brassica rapa subspecies, pekinensis) to its effectiveness in Staphylococcus aureus. This research is experimental laboratory. Concentration of chicoryin soap are 0%, 25%, 50%, 75% and 100%. Anti-bacterial effectivenesstest was performed by disc method of transparent antibacterial soap of chicory extract of ethanol (Brassica rapa subspecies, pekinensis) and measured the clear zone. The analysis was performed by Two Way ANOVA test. The results of soap quality assurance standard fulfill quality standard specified by SNI in 1994 that water content test is found in formulation 6 (F6) with 75% concentration equal to 2.109%. The best free alkali test result were found in the formulation 5 (F5) with a 25% concentration of 0.041963, 50% by 0.041966 and 100% by 0.041963. The best free fatty acid test result were found in the formulation of 2 (F2) 50% concentration with free fatty acid level of 0.07852 %. For thebest pH test the conceration of 0%, 25% and 50% with pH yielded 9 and the best foam high yield test was found at 100% concentration. Result of Two Way ANOVA test with variation of extract concentration of chicory ethanol and combination of coconut oil and castor oil obtained p-value = 0.000 <0.05 which states there is real difference. The best test results are in F6 (30.6833 mm). Two Way ANOVA test results showed that transparentsolid soaps of chicory extracts had the best antibacterial effectiveness against Staphylococcus aureus with an inhibitory zone of 30.6833 mm at 100% concentration.